GİRİŞİMCİLİK EĞİLİMLERİNİN BELİRLENMESİ: TAŞKENT MYO ÖĞRENCİLERİ ÜZERİNE BİR ARAŞTIRMA - DETERMINATION OF ENTREPRENEURSHIP TRENDS: A STUDY ON TAŞKENT VOCATIONAL SCHOOL STUDENTS - Ayşe Yavuz; Halil İbrahim Yavuz (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Entrepreneurship;Labor, capital and natural resources, bringing goods or services to thefruitful activities of the general name given to the activities. The entrepreneuris the person who carries out these activities. With this study, it is aimed toreveal the entrepreneurship tendencies of the students in vocational schools.Thus, the interests and competences of the students for entrepreneurship willbe opened. This study was carried out on Selçuk University Taşkent VocationalSchool students. Survey technique was used as data collection tool. Theobtained data were analyzed by SPSS packet program. As a result of the study,demographic characteristics of students and entrepreneurship tendencies arerelated and entrepreneurship levels of students are revealed.